Harvesting sorghum stover - G.E. Fairbanks; J.D. Hoover (Kansas Agricultural Experiment Station Research Reports, 1976)
Two types of big round balers and a small stackmaker were used to harvest grain sorghum stubble after the grain was harvested during the fall and winter months of 1975. The stubble was about 21 inches high and about 4 inches of stubble was left after windrowing.
Keywords: Cattlemen& #x27; s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Sorghum stover; Round baler